A 2D substrate integrated waveguide monopulse slot antenna array with dual‐mode comparator. Issue 12 (28th October 2022) - Sun, Zhichao; Liu, Shaobin; He, Wenhui; An, Tong; Hu, Zhiyong; Yang, Yuning; Zheng, Xinyuan
Abstract: A double‐layer 2D substrate integrated waveguide monopulse slot antenna array is proposed. By adopting the dual‐mode monopulse comparators (DMCs), the isolations between ports are significantly improved. The antenna generates "sum" and "difference" patterns in the orthogonal axis with a pair of DMCs. The DMC for azimuth plane tracking and the radiating 4 × 4 slots are located on the top layer, and another DMC is on the bottom layer for the elevation plane tracking and feeds the slot array through two coupling slots. Based on the proposed antenna, an antenna prototype is fabricated. The measured −10 dB shared impedance bandwidth for four ports is 6.18% (9.4–10 GHz) and the isolations between ports are better than 27 dB. The null depths of the difference patterns are lower than −35 dB. The measured results are in good agreement with the simulated results.